Functional characterization of three ABC1-like kinases found in the plastoglobule proteome - Martinis, Jacopo (My University, 2012)
In bacteria and mitochondria, the members of the ABC1/ADCK/UbiB family regulate ubiquinone synthesis, and their mutations cause severe respiration defects, including progressive neurological disorders in humans. Little is known about plant ABC1-like kinases: in Arabidopsis thaliana five are predicted in mitochondria, but surprisingly six are located at lipid droplets (plastoglobules) in chloroplasts. These are a known site of carotenoid (β-carotene, lutein) and prenylquinone (including Vitamin E, K and plastoquinone) metabolism and contain a large proportion of the tocopherol cyclase (VTE1) required for Vitamin E synthesis and Redox recycling. Although the key enzymes involved in carotenoid and prenylquinone biosynthesis are mostly known, the regulation of these pathways is still poorly understood. Therefore, ABC1-like kinases may be suitable candidates for such regulators and be involved in the modulation of chloroplast lipid metabolism.
Using a non-targeted lipidomics approach we demonstrate that plants lacking either of the plastoglobule kinase ABC1I (At1g79600) or ABC1k3 (At4g31390) are defective both in the production of tocopherols and plastochromanol-8 (a plastoquinone-derived lipid antioxidant) as well as in the Redox recycling of α-tocopherol (Vitamin E). All of these pathways require tocopherol cyclase (VTE1) activity. However, in both mutants VTE1 levels are strongly reduced post-transcriptionally. Our results strongly indicate that both kinases are directly involved in the regulation of the activity of the tocopherol cyclase VTE1, likely by phosphorylation. This may stabilize VTE1 levels at plastoglobules or influence its activity.
At the same time, we demonstrate that the plastoglobule kinase ABC1k3 is allelic to the photosynthetic mutant pgr6, identified in a screening of A. thaliana plants with low NPQ, possibly because of a low carotenoid content. The abc1k3/pgr6 mutant is also characterized by a defect in Fv/Fm and ETR after short high light treatment. Remarkably however, mutant plants are able to acclimate to high light, concurrently with a recovery in the cellular content of the xanthophylls lutein and β-carotene and a drastic alteration in the starch-to-sucrose ratio.
A knock-down mutant line for a third kinase, ABC1V (At5g05200), was also produced and subjected to preliminary characterization.
In conclusion, our results indicate that plastoglobule ABC1-like kinases may regulate prenylquinone, carotenoid and sugar metabolism and that VTE1 is a highly probable kinase substrate. However, the ABC1-like kinases may also have other targets and thereby act as major regulators in a wide chloroplast regulatory network.
Thèse de doctorat : Université de Neuchâtel, 2012
Keywords: Chloroplastes; Cellules végétales; Biologie moléculaire végétale; ABC1-like kinases; Plastoglobules; Carotenoids; Tocopherols; Plastochromanol; Photosynthesis; VTE1